PENGEMBANGAN MEDIA PADA PEMBELAJARAN MENYIMAK UNSUR INTRINSIK DENGAN MODEL COOPERATIVE LEARNING TIPE NUMBERED HEAD TOGETHER (NHT) - Suroyani, Atik (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
Learning Media as studying source is learning system component that can influence the study result and motivate the student. The aims of this research are describe audio visual development process in, the quality of, and the implementation of intrinsic element listening learning using Cooperative Learning Model Numbered Head Together (NHT) Type for the XII grade Student of MAN. This is a research and development that is the research method used to produce certain product. In this development audio visual media, there are seven development processes that have been carried out. The quality of audio visual media fulfills validity, practicality, and effective aspects and the implementation of audio visual based on the teacher activity and the result of observation of student activity.